Shaping the human gut microbiota: The role of canine companionship, lifestyle choices, and Blastocystis sp - Pavlíčková, Zuzana; Pafčo, Barbora; Ilík, Vladislav; O'Brien Andersen, Lee; Jirků, Milan; Brožová, Kristýna; Modrý, David; Kadlecová, Oldřiška; Stensvold, Christen Rune; Jirků, Kateřina (One health, 2025)
External factors affecting composition of the human gut microbiota have attracted considerable attention in recent years. Among these factors, habitat sharing with other humans and companion animals, especially dogs, is considered crucial together with the presence of intestinal protists. The Czech Republic, known for one of the highest rates of dog ownership in Europe, provides an ideal setting for studying such relationships. Here, we investigated the impact of dog ownership and lifestyle factors (residing in cities versus villages) on the gut microbiota (specifically bacteriome). In addition, we also investigated the influence of the common gut protist Blastocystis sp. on the human gut microbiota. Fecal DNAs from 118 humans and 54 dogs were subject to 16S rRNA gene sequencing using the Illumina MiSeq platform. Greater microbial diversity was observed in humans than in dogs. Owning a dog had no significant effect on the alpha and beta diversity of the human microbiota, although some bacterial genera were enriched in dog owners. In relation to lifestyle, urban dwellers had higher levels of Akkermansia, while people living in villages had a more diverse gut microbiota. The presence of Blastocystis sp. in humans correlated with specific microbial patterns, indicating an important role for this micro-eukaryote in the gut ecosystem. These findings highlight the intricate relationship between specific factors and the gut microbiota composition and emphasize the need for more extensive research in this area.